Late Carboniferous–early Permian arc magmatism in the south‐western Alxa Tectonic Belt (NW China): Constraints on the late Palaeozoic subduction history of the Palaeo‐Asian Ocean. (21st October 2018) - Song, Dongfang; Xiao, Wenjiao; Collins, Alan; Glorie, Stijn; Han, Chunming
Abstract : The tectonic setting of the Alxa Tectonic Belt (ATB) during the late Palaeozoic is highly controversial. The nature and tectonic origin of the late Palaeozoic magmatism in the ATB are key to resolving the current controversy. This paper provides field, petrographic, geochemical, and zircon U‐Pb‐Hf isotopic data for the late Palaeozoic granitoids and volcanic rocks from the south‐western ATB. The granitoids display a wide range of SiO2 contents from diorite, granodiorite, to granites, with widely distributed hydrous minerals such as hornblende and biotite. They are calc‐alkaline to high‐potassium calc‐alkaline, metaluminous with an enrichment of light rare earth elements and large‐ion lithophile elements (LILE), and a depletion of high‐field‐strength elements (HFSE). The presence of mafic‐intermediate enclaves in the plutons suggests the role of crust–mantle interaction in generating the granitoids. The volcanic rocks show "block‐in‐matrix" structures in the field. They are dacite‐porphyry and rhyolite and show calc‐alkaline characteristics with an enrichment of LILE and a depletion of HFSE. Laser ablation inductively coupled plasma mass spectrometry zircon U‐Pb dating shows that the granitoids and enclaves crystallized during ~317–287 Ma and the dacite porphyry formed at ~295 Ma. Hf‐in‐zircon isotopic compositions reveal predominately positive εHf ( t ) values and Neoproterozoic TDM C ages for the magmatic rocks, indicating mixing between mantle‐derived magma and Precambrian basement during their genesis. The diagnostic field, geochemical data, and isotopic data imply these rocks were generated in a subduction‐related active continental margin setting. The presence of A2 ‐type granite indicates an extensional environment resulted from slab rollback in a retreating accretionary context can best interpret the large‐scale late Carboniferous–early Permian magmatism in the ATB. Our new data, combined with published data, imply that a large active continental margin existed in the Beishan, Alxa, and the northern margin of the North China Craton, due to the south‐dipping subduction of the Palaeo‐Asian Ocean (PAO) in the late Palaeozoic. Therefore, our data suggest that the PAO did not close until after the early Permian.